Effects and prevalence of nonresponders after 12 weeks of high-intensity interval or resistance training in women with insulin resistance: A randomized trial (2017)
Our aim was to investigate the effects and prevalence of nonresponders (NR) to high-intensity interval training (HIIT) and resistance training (RT) in women with insulin resistance on cardiometabolic health parameters. Sedentary overweight/obese insulin-resistant women (age = 33.5 ± 6.5 yr; body mass index = 29.9 ±3.7 kg/m2) were randomly assigned to a triweekly HIIT program (HIIT; n = 18) or resistance training (RT; n = 17). Anthropometry (body mass, fat mass, muscle mass, waist circumference, and skinfold thickness), cardiovascular (blood pressure), metabolic [fasting glucose, fasting insulin, and homeostatic model of insulin resistance (HOMA-IR)], as well as muscle strength, and endurance performance covariables were measured before and after 12 wk in both intervention groups. The interindividual variability to exercise training of the subjects was categorized as responders and NR using as cut points two times the typical error of measurement in mean outcomes. After intervention, significant reduction in waist circumference, skinfold thicknesses, fat mass, blood pressure, fasting glucose, insulin, and HOMA-IR (P and lt; 0.05) were identified to HIIT and RT group, respectively. Both HIIT and RT groups exhibited a significant decrease in the endurance performance, whereas only RT exhibited increased muscle strength. Significant differences in the NR prevalence between the HIIT and RT groups were identified for a decrease in fat mass (HIIT 33.3% vs. RT 70.5%; P = 0.028), muscle mass (HIIT 100% vs. RT 52.9%; P = 0.001), and tricipital skinfold (HIIT 5.5% vs. RT 29.4%; P and lt; 0.041). For diastolic blood pressure, significant differences were observed in the NR prevalence between the HIIT and RT groups (55.5% vs. 94.1; P = 0.009). However, there were no differences in the NR prevalence between HIIT and RT for decreasing fasting glucose. Twelve weeks of HIIT and RT have similar effects and NR prevalence to improve glucose control variables; however, there is different NR prevalence in other anthropometric, cardiovascular, strength, and endurance performance measurements in insulin-resistant women. These findings were displayed with a similar time investment per week of 114 vs. 108 min, respectively, to HIIT and RT. Copyright © 2017 the American Physiological Society.